The Effect of Tai Chi Feedback Teaching on the Academic Performance of Students at Nantong Institute of Technology - Zhihao, Zou; Promthep, Kreeta; Eakronnarongchai , Wiradee; Khantiyu , Yodkhwan (Journal of Roi Kaensarn Academi, 2024)
The purpose of this study is as follows:1) Compare students’ learning status before and after students learn. Students in the experimental group receive Tai Chi feedback teaching, while students in the control group receive normal Tai Chi teaching; This paper is a quantitative study. The samples were 40 students from Class 3 and Class 4 in the martial arts class of freshmen in Nantong Institute of Technology. They were selected by them before the experiment with the same athletic ability and Tai Chi learning ability. PASS software was used to calculate the sample size, and 22 students were selected from two classes respectively as the final experimental group and control group of this study. The experimental group lesson plan developed by the researcher was tested by 4 experts. The results show that:1) Comparing with traditional teaching method is significantly different from traditional teaching at 0.05 Tai Chi feedback teaching method can improve students’ performance of Tai Chi through experiment. Conclusion Through the experiment, feedback teaching curriculum design, make students become the main body of the class, improve students’ participation in the class, and then can effectively break through the important and difficult movements, improve the performance of Tai Chi.